EXPLORATION OF THE APPLICATION OF HEALTH AND SPORTS PHYSICAL EDUCATION LEARNING IN SCHOOLS: A LITERATURE STUDY - Fauzi, Muhammad Sukron; Julianur, Julianur; Judijanto, Loso; Prananda, Gingga (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
The aim of this research is to explore the implementation of health and sports physical education learning in schools. This research is research using the literature study or literature review method. To conduct this research, the researchers used various search engines such as ProQuest, PubMed, ResearchGate, SagePub, and Scholar to search for online research journals. In the field of school education, sports physical education plays an important role by offering students the opportunity to actively engage in systematic physical activity and share their learning experiences. These experiences aim to encourage physical growth, psychological development, and the adoption of a healthy and active lifestyle throughout one's life. The effectiveness of physical education and sports teaching can, among other things, be assessed through the availability of adequate facilities and infrastructure. The existence of adequate facilities and infrastructure reflects the quality of the educational experience, which ultimately leads to the successful achievement of educational goals.